Mood and Balance are Associated with Free-Living Physical Activity of People after Stroke Residing in the community. (13th October 2011) - Alzahrani, Matar A.; Dean, Catherine M.; Ada, Louise; Dorsch, Simone; Canning, Colleen G.
Abstract : Purpose . To determine which characteristics are most associated with free-living physical activity in community-dwelling ambulatory people after stroke. Method . Factors (age, gender, side of stroke, time since stroke, BMI, and spouse), sensory-motor impairments (weakness, contracture, spasticity, coordination, proprioception, and balance), and non-sensory-motor impairments (cognition, language, perception, mood, and confidence) were collected on 42 people with chronic stroke. Free-living physical activity was measured using an activity monitor and reported as time on feet and activity counts. Results . Univariate analysis showed that balance and mood were correlated with time on feet (r = 0.42, 0.43, P < 0.01 ) and also with activity counts (r = 0.52, 0.54, P < 0.01 ). Stepwise multiple regression showed that mood and balance accounted for 25% of the variance in time on feet and 40% of the variance in activity counts. Conclusions . Mood and balance are associated with free-living physical activity in ambulatory people after stroke residing in the community.